COMPARATIVE ANALYSIS OF THE TRADITIONAL ISLAMIC EDUCATION SYSTEM AND THE MODERN ISLAMIC EDUCATION SYSTEM IN INDONESIA - Aminullah, Muhammad; Rama, Bahaking; Miro, Abbas Baco; Rijal, Tabhan Syamsu (Universitas Islam Negeri Alauddin Makassar, 2024)
The research aims to analyze the comparison of the traditional Islamic education system with the modern Islamic education system in Indonesia. The results of this research show that the traditional Islamic education system in Indonesia is education carried out by educators using old methods. Traditional Islamic education is known as the Halaqah system and does not use alternatives such as benches, tables and blackboards. While the modern Islamic education system in Indonesia is education that is based on the concept of divinity but is universal, modern Islamic education does not only focus on religious lessons but is also integrated with science and technology with a classical system, namely using tables, chairs, blackboards and other learning media. The comparison between these two systems is found in their educational institutions. In the curriculum aspect, traditional Islamic education has its curriculum from the kyai or top leaders of the institution, while the curriculum in modern Islamic education is an integrated curriculum from educational institutions (Mendikbutristek) and religious institutions (Kemenag).